2012
DOI: 10.1289/ehp.1104776
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid-Mediated Quinolone Resistance Genes and Antibiotic Residues in Wastewater and Soil Adjacent to Swine Feedlots: Potential Transfer to Agricultural Lands

Abstract: Background: Inappropriate use of antibiotics in swine feed could cause accelerated emergence of antibiotic resistance genes, and agricultural application of swine waste could spread antibiotic resistance genes to the surrounding environment.Objectives: We investigated the distribution of plasmid-mediated quinolone resistance (PMQR) genes from swine feedlots and their surrounding environment.Methods: We used a culture-independent method to identify PMQR genes and estimate their levels in wastewater from seven s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(80 citation statements)
references
References 37 publications
6
62
0
6
Order By: Relevance
“…It has been some years since Iwane and colleagues [23] showed that the increase of antibiotic resistant bacteria in the Tama River was associated with WWTP effluent discharges. Since then, a wide range of genetic methods have been developed and some culture-independent studies have been performed to explore the impact of antibiotics in the environment; however, most of these studies have been limited to a few ARGs [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…It has been some years since Iwane and colleagues [23] showed that the increase of antibiotic resistant bacteria in the Tama River was associated with WWTP effluent discharges. Since then, a wide range of genetic methods have been developed and some culture-independent studies have been performed to explore the impact of antibiotics in the environment; however, most of these studies have been limited to a few ARGs [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the ARGs were closely linked with a number of widespread mobile genetic elements (MGEs), including plasmids, transposons and integrons, which were involved in horizontal transfer of ARGs among environmental bacteria (Fluit and Schmitz, 1999;Fricke et al, 2009;Li et al, 2012;. These ARGs could be missed when screening a microbial chromosomal DNA derived metagenomic library.…”
Section: Tetracycline Resistancementioning
confidence: 99%
“…Riverine ARGs were correlated with human activities (Pruden et al, 2012). Evidences suggested that human affecting compartments, such as wastewater treatment plants, animal feedlots and pharmaceutical factories were as significant point sources of ARGs into the receiving water bodies (Graham et al, 2010;LaPara et al, 2011;Li et al, 2012), which may also explain the reason why high contaminations of ARGs were observed in the Liuxi River. Besides antibiotics, metals also co-select for ARGs (Knapp et al, 2011).…”
Section: Discussionmentioning
confidence: 99%